An Analysis of the Undergraduate Program of the Police School of the University of Internal Affairs - Ragchaasuren, Bayarmagnai; Tsend, Bayarmaa (Lavai - International Journal of Education, 2024)
Theoretical knowledge, skills, and practical experience of the cadets, students, and graduates are essential for the implementation of the basic functions of the police organization to effectively combat crime, maintain public order, and ensure public safety. However, all of these depend on the concept of educational programs, training theories, and development trends. Therefore, we have written this article to analyze the undergraduate programs and their implementation, and to propose some improvements. The research focuses on the analysis of the undergraduate curriculum methodology at the Police School of the Internal Affairs University of Mongolia from 2000 to 2019. It involves comparing the current four specialized programs with those of the national police universities of the Russian Federation and the Republic of Korea. After conducting the analysis, we identified both problems and opportunities. We surveyed 250 graduates of the programs to compare the quality and accessibility of education at that time to the current situation which helped us identify the issues. According to the survey, 75 percent of the respondents believe that the Police Work-Law undergraduate program needs to be improved and updated while the remaining 20 percent did not feel that it needed improvement, and 5 percent were unsure. Comparative analysis of the programs finds that there has been an increase in program content and credit hours, some courses overlap, the internship period is short, and the quality and results are weak. Upon comparing similar programs in other countries, it has been identified that implementing curricula in areas such as artificial intelligence, coding, and programming can help international law schools effectively meet the challenges of 21st-century legal practice.